Program for Learning the Pronunciation of Phonemes for Children with Hearing Impairment at SLBN Cileunyi - Lamina Amalia Putri; Oom Sitti Homdijah; Dudi Gunawan; Budi Susetyo (Edumaspul: Jurnal Pendidikan, 2023)
Based on preliminary observations at SLBN Cileunyi, the errors the pronunciation of phonemes were found in children with hearing impairments in grade 3 elementery school of SLBN Cileunyi. This happens because of the impact of hearing loss experienced by them. Schools have made efforts to practice the pronunciation of phonemes that are integrated into learning activities, but the planning and implementation of learning are still not optimal. The purpose of this study was to develop a program for learning the pronunciation of phonemes for children with hearing impairments at SLBN Cileunyi. This study uses a qualitative approach with a case study research design. The program was developed based on empirical and theoretical studies which were then validated by experts. This program contains the scope of warm-up exercises for articulation and respiratory organs, phoneme formation exercises, and phoneme improvement exercises. This research resulted in a program for learning the pronunciation of phonemes which was made based on the needs of children and the objective conditions of the school and based on the supporting theory. Through this program, it is hoped that teachers can carry out learning to pronounce phonemes well and in a planned manner based on the needs of the child.